2002
DOI: 10.1093/carcin/23.12.2063
|View full text |Cite
|
Sign up to set email alerts
|

Development and molecular characterization of HCT-116 cell lines resistant to the tumor promoter and multiple stress-inducer, deoxycholate

Abstract: Evidence from live cell bioassays shows that the flat mucosa from patients with colon cancer exhibits resistance to bile salt-induced apoptosis. Three independent cell lines derived from the colonic epithelial cell line HCT-116 were selected for resistance to bile salt-induced apoptosis. These cell lines were developed as tissue culture models of apoptosis resistance. Selection was carried out for resistance to apoptosis induced by sodium deoxycholate (NaDOC), the bile salt found in highest concentrations in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 147 publications
4
60
0
Order By: Relevance
“…Hydrophobic bile acids, such as deoxycholic acid (DCA, model bile acid), induce apoptosis after acute exposure (3). In contrast, chronic exposure of epithelial cells to bile acids leads to the selection of clones with an apoptosis-resistant phenotype (1). Similarly, we reported in our recent paper, the acute exposure to relatively low concentrations of DCA leads to normal cellular response, the induction of autophagy, and increased Beclin-1 expression, but chronic exposure to DCA does not affect Beclin-1 expression and results in defective autophagy (5).…”
supporting
confidence: 66%
“…Hydrophobic bile acids, such as deoxycholic acid (DCA, model bile acid), induce apoptosis after acute exposure (3). In contrast, chronic exposure of epithelial cells to bile acids leads to the selection of clones with an apoptosis-resistant phenotype (1). Similarly, we reported in our recent paper, the acute exposure to relatively low concentrations of DCA leads to normal cellular response, the induction of autophagy, and increased Beclin-1 expression, but chronic exposure to DCA does not affect Beclin-1 expression and results in defective autophagy (5).…”
supporting
confidence: 66%
“…An increasing amount of evidence suggest that bile acids may be a multiple stress-inducer (Crowley-Weber et al 2002), and one of the best-documented pathways is the one involving protein kinase C (PKC) (Debruyne et al 2001). Recently, many researchers reported that DCA might activate the Ras/Raf/ERK kinase pathway, then subsequently up-regulate some genes downstream (Yoon et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Target Preparation-Microarray analysis was done as described before (41). In short, the RNeasy total RNA kit (Qiagen, Valencia, CA) and protocol was used to isolate total RNA from the Caco-2 cells treated with either vehicle or sulindac sulfone.…”
Section: Cdna Microarray Analysismentioning
confidence: 99%